Coordination and adaptation of water processes in Populus euphratica in response to salinity - Li, Duan; Si, Jianhua; Ren, Xiaozong (Frontiers in Plant Science, 2024)
Water processes secure plant survival and maintain their ecosystem function.Salinity affects water processes, but the mechanisms remain unclear and may depend on the degree of salinity stress. To improve the understanding of the cooperation of plant organs involved in water processes under salinity stress, we determined hydraulic, gas exchange, and physiological and biochemical parameters in Populus euphratica Oliv. (P. euphratica) under different salinity stresses. The results suggested that P. euphratica enhanced water transport efficiency in a salinity-stress environment, and the strengthening effect of roots in the water transfer process was greater than that of the aboveground parts.P. euphratica also increased water use efficiency and water transport efficiency in mild and moderate salinity stress (less than 200 mmol/L NaCl) but was adversely affected by heavy salinity stress (more than 300 mmol/L NaCl). Furthermore, P. euphratica increased its water storage by regulating antioxidant enzyme scavenging capacity and osmoregulation, which resulted in coordinated greater water utilization and enhanced water transport among plant organs and indicated that the adverse effects on water processes triggered by salinity stress depended on the extent of salt stress. P. euphratica lessened stress-induced damage and maintained plant productivity by coordination and cooperation of water processes under certain levels of salinity. Research on the coordination and cooperation involving water processes in riparian forests in saline areas provides the scientific basis for riparian plant protection and restoration.